2017
DOI: 10.1111/jnc.13955
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and its active metabolites inhibit dopamine transporter function independently of the estrogen receptors

Abstract: As one of the primary mechanisms by which dopamine signaling is regulated, the dopamine transporter (DAT) is an attractive pharmacological target for the treatment of diseases based in dopaminergic dysfunction. In this work we demonstrate for the first time that the commonly prescribed breast cancer therapeutic tamoxifen and its major metabolites, 4-hydroxytamoxifen and endoxifen, inhibit DAT function. Tamoxifen inhibits [ H]dopamine uptake into human DAT (hDAT)-N2A cells via an uncompetitive or mixed mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…In a recent study, Mikelman et al show that tamoxifen interacts with the dopamine transporter (DAT) and can block amphetamine‐stimulated dopamine release as well as blocking dopamine reuptake in rat synaptosomes . While acute tamoxifen exposure did not change locomotor behavior, it was effective at blocking the locomotor‐stimulating effects of amphetamine . It is possible that the neonatal DAT stimulation by tamoxifen caused the mild hyperactivity when the mice were tested as adults, though it is also possible that modulation of the estrogen receptor played a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Mikelman et al show that tamoxifen interacts with the dopamine transporter (DAT) and can block amphetamine‐stimulated dopamine release as well as blocking dopamine reuptake in rat synaptosomes . While acute tamoxifen exposure did not change locomotor behavior, it was effective at blocking the locomotor‐stimulating effects of amphetamine . It is possible that the neonatal DAT stimulation by tamoxifen caused the mild hyperactivity when the mice were tested as adults, though it is also possible that modulation of the estrogen receptor played a role.…”
Section: Discussionmentioning
confidence: 99%
“…36 While acute tamoxifen exposure did not change locomotor behavior, it was effective at blocking the locomotorstimulating effects of amphetamine. 36,37 It is possible that the neonatal DAT stimulation by tamoxifen caused the mild hyperactivity when the mice were tested as adults, though it is also possible that modulation of the estrogen receptor played a role. Together, these data add to the growing literature that behavioral studies employing tamoxifen, especially those looking at dopamine-modulated behaviors, should always include vehicle-treated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is a widely prescribed selective estrogen receptor modulator (SERM) used in the treatment and prevention of estrogen receptor-positive breast cancer (Jordan, 2014). It has long been known that the drug tamoxifen affects the dopaminergic system, yet the mechanisms by which it does so have remained unclear (Mikelman et al, 2017). Tamoxifen causes a small but significant increase in extracellular dopamine levels in the nucleus accumbens after peripheral administration (Chaurasia et al, 1998) and also inhibits amphetamine-stimulated hyperactivity (Einat et al, 2007;Cechinel-Recco et al, 2012;Pereira et al, 2014), which relies on elevation of extracellular dopamine levels in the striatum (French, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The DAT is responsible for clearing dopamine from the extracellular space after its release and in this capacity is a crucial mechanism for regulating dopaminergic signaling (Jaber et al, 1997). Although tamoxifen was shown to block amphetamine-stimulated locomotor behavior (Einat et al, 2007) and we previously demonstrated that it inhibits DAT function independently of its action as an SERM (Mikelman et al, 2017), no studies reported to date have systematically examined the interaction between tamoxifen and the DAT.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Mikelman et al show that tamoxifen interacts with the dopamine transporter (DAT) and can block amphetamine-stimulated dopamine release as well as blocking dopamine reuptake in rat synaptosomes (Mikelman et al 2018). While acute tamoxifen exposure did not change locomotor behavior, it was effective at blocking the locomotor-stimulating effects of amphetamine (Mikelman et al 2017;Mikelman et al 2018). It is possible that the neonatal DAT stimulation by tamoxifen caused the mild hyperactivity when the mice were tested as adults, though it is also possible that modulation of the estrogen receptor played a role.…”
Section: Discussionmentioning
confidence: 99%